Electrospun Li(TFSI)@Polyethylene Oxide Membranes as Solid Electrolytes. Issue 24 (27th November 2018) - Walke, Patrick; Freitag, Katharina M.; Kirchhain, Holger; Kaiser, Matthias; van Wüllen, Leo; Nilges, Tom
Abstract : Thin membranes of lithium‐bis(trifluoromethan)sulfonimide@poly (ethylene oxide) (or Li(TFSI)@PEO) were fabricated by electrospinning from acetonitrile solutions of the starting materials at room temperature. Membranes were tested with and without succinonitrile (SN), acting as a plasticizer to enhance the ion mobility in the systems. Our experiments substantiate, that SN does influence the electrochemical performance and physical properties of the membranes. Homogeneous amorphous membranes were only realized for SN‐containing samples, while phase segregation and crystallization occurred for SN‐free representatives. Membranes of different compositions were tested and the optimum molar mixture of PEO:SN:Li(TFSI), in terms of membrane conductivity, was identified as 36:8:1. Conductivities up to up to 2.8 × 10 –4 S· cm –1 were determined by impedance spectroscopy for this membrane. Used as solid electrolytes without the aid of any additional electrolyte in symmetric Li vs. Li cells, a reasonable stability upon Li cycling could be observed. Here we illustrate that electrospun plasticizer‐modified Li(TFSI)@PEO membranes show high conductivities at very low conductive salt concentrations, compared with solution casted or hot pressed representatives. This feature renders these materials as potential candidates for separators in all solid‐state batteries or related energy storage applications. Abstract :